2015
DOI: 10.1038/tpj.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

NUDT15 R139C causes thiopurine-induced early severe hair loss and leukopenia in Japanese patients with IBD

Abstract: The efficacy of thiopurines, including azathioprine (AZA) and 6-mercaptopurine (6MP), has been demonstrated for the treatment of inflammatory bowel disease (IBD). The most common and serious adverse event of treatment with thiopurines altered by doctors is leukopenia. Hair loss is also a serious event that could be a critical reason for patients to decline thiopurine treatment. Thiopurine-induced severe hair loss causes cosmetic problems, and it takes a long time to recover. In a recent study, NUDT15 R139C was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
179
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 24 publications
15
179
1
Order By: Relevance
“…In contrast, NUDT15 genetic variation is substantially over-represented in Asians and is their predominant genetic cause for thiopurine toxicity 46,47 . The unequivocal evidence linking NUDT15 p.Arg139Cys variant to thiopurine toxicity (particularly in Asians 46,47,49,50 ) strongly indicates its potential clinical relevance, and also raises the question of whether (or what) clinical action is warranted for these at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NUDT15 genetic variation is substantially over-represented in Asians and is their predominant genetic cause for thiopurine toxicity 46,47 . The unequivocal evidence linking NUDT15 p.Arg139Cys variant to thiopurine toxicity (particularly in Asians 46,47,49,50 ) strongly indicates its potential clinical relevance, and also raises the question of whether (or what) clinical action is warranted for these at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that the risk–benefit profile of immunosuppressants therapy is different in Japanese patients compared to Western patients [24, 25, 34], and thus, in the real-world setting, physicians may be cautious on adding immunosuppressant. Furthermore, the results showed that among patients treated with IFX, there was a significantly higher probability of dose escalation in patients who were prescribed immunosuppressant therapy compared to those without immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…The database was completely anonymized and contained patient demographic information (gender, age, insurance type, and reason of withdrawal), inpatient and outpatient medical and pharmacy claims data, with clinical diagnoses coded under the International Classification of Diseases 10th revision (ICD-10) classification [23], Japan-specific standard disease codes [24], drug prescriptions information coded according to the Anatomical Therapeutic Chemical (ATC) classification, as well as health care procedures defined using Japan-specific standardized procedure codes [25, 26]. …”
Section: Methodsmentioning
confidence: 99%
“…158 This SNP is rare in European ancestry individuals but is also associated with thiopurine-induced leukopenia in Europeans and the association with bone marrow toxicity has also been reproduced in Japanese IBD patients. 158,161,162 Pancreatitis is one of the dose-independent adverse reactions related with thiopurines limiting their use in IBD. 157 In a recent worldwide study to identify genetic markers predicting pancreatitis within 3 months of starting thiopurines in patients with IBD, a GWAS on 172 cases and 2035 controls as well as additional validation was performed.…”
Section: Pharmacogenetics Associated With Ibd Therapymentioning
confidence: 99%